2009
DOI: 10.1099/vir.0.004614-0
|View full text |Cite
|
Sign up to set email alerts
|

Broad, high-magnitude and multifunctional CD4+ and CD8+ T-cell responses elicited by a DNA and modified vaccinia Ankara vaccine containing human immunodeficiency virus type 1 subtype C genes in baboons

Abstract: Candidate human immunodeficiency virus (HIV) vaccine regimens based on DNA boosted with recombinant modified vaccinia Ankara (MVA) have been in development for some time, and there is evidence for improved immunogenicity of newly developed constructs. This study describes immune responses to candidate DNA and MVA vaccines expressing multiple genes (gag, RT, tat, nef and env) from HIV-1 subtype C in chacma baboons (Papio ursinus).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 67 publications
3
26
0
Order By: Relevance
“…Indeed, CD8+ T-cells with pluripotent functions have been shown to be more effective at controlling infectious pathogens. 3,4,6,22 Consistent with these reports, following ex vivo or in vitro stimulation with HCMV epitopes, CD8 + T-cells from immunised mice showed strong IFN-␥ expression and a large proportion of these T-cells also expressed TNF-␣ and/or CD107␣ ( Fig. 2A), demonstrating that the Ad-gBCMVpoly vaccine can induce pluripotent T-cells.…”
Section: Immunogenicity and Efficacy Of Ad-gbcmvpoly Vaccinesupporting
confidence: 83%
“…Indeed, CD8+ T-cells with pluripotent functions have been shown to be more effective at controlling infectious pathogens. 3,4,6,22 Consistent with these reports, following ex vivo or in vitro stimulation with HCMV epitopes, CD8 + T-cells from immunised mice showed strong IFN-␥ expression and a large proportion of these T-cells also expressed TNF-␣ and/or CD107␣ ( Fig. 2A), demonstrating that the Ad-gBCMVpoly vaccine can induce pluripotent T-cells.…”
Section: Immunogenicity and Efficacy Of Ad-gbcmvpoly Vaccinesupporting
confidence: 83%
“…The data presented here suggest that CSFV-specific IFN-␥-expressing cells may also have cytotoxic capacity and consolidate our previous results where we showed that IFN-␥ expression was restricted to CD8 T cells expressing intracellular perforin (7) and other earlier studies that demonstrated CSFV-specific cytotoxic activity by T cell cultures isolated from vaccinated pigs (8)(9)(10). While IFN-␥-secreting T EM cells have been implicated in protection against a variety of intracellular pathogens, simultaneous production of IFN-␥, TNF-␣, and IL-2 detected at the single-cell level by multiparameter flow cytometry has been correlated with enhanced vaccine-induced protection (45)(46)(47)(48)(49)(50)(51). Moreover, data suggest that such polyfunctional CD8 T memory cells are critical to long-term protection against other viruses belonging to the family Flaviviridae (20,22).…”
Section: Discussionmentioning
confidence: 99%
“…These vaccines were extensively characterised at UCT by means of expression studies, investigations of potency and stability, and mouse and non-human primate immunogenicity studies. 9,10 In order to monitor the potency of SAAVI DNA-C2 during a clinical trial, a laboratory compliant with the Organisation for Economic Co-operation and Development (OECD) principles of good laboratory practice (GLP) was established, the only one in an academic setting in SA. Immunogenicity endpoints were measured at days 126 and 154 (2 weeks following the first and second MVA vaccinations).…”
Section: Vaccines For Clinical Trialmentioning
confidence: 99%